2013
DOI: 10.1016/j.biopsych.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Glucocorticoid Exposure Is Associated with Preadolescent Brain Development

Abstract: Background Glucocorticoids play a critical role in normative regulation of fetal brain development. Exposure to excessive levels may have detrimental consequences and disrupt maturational processes. This may especially be true when synthetic glucocorticoids are administered during the fetal period, as they are to women in preterm labor. The present study investigated the consequences for brain development and affective problems of fetal exposure to synthetic glucocorticoids. Methods Brain development and aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
153
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(169 citation statements)
references
References 109 publications
11
153
1
2
Order By: Relevance
“…Specifically, children aged 6-10 years old with synthetic fetal glucocorticoid exposure were found to have a thinner cortex primarily in the rostral anterior cingulate cortex (rACC). Separately, studies have reported that the thinner left rACC cortex was associated with offspring affective problems (Davis et al, 2013) and that prenatal synthetic glucocorticoid treatment was associated with offspring general psychiatric disturbance (Khalife et al, 2013). These data support the hypothesis that aberrant glucocorticoid signaling in the fetal environment, potentially associated with prenatal stress in mothers, alters neuroanatomical development, contributing to behavioral problems in offspring.…”
Section: Neuroanatomicalsupporting
confidence: 56%
“…Specifically, children aged 6-10 years old with synthetic fetal glucocorticoid exposure were found to have a thinner cortex primarily in the rostral anterior cingulate cortex (rACC). Separately, studies have reported that the thinner left rACC cortex was associated with offspring affective problems (Davis et al, 2013) and that prenatal synthetic glucocorticoid treatment was associated with offspring general psychiatric disturbance (Khalife et al, 2013). These data support the hypothesis that aberrant glucocorticoid signaling in the fetal environment, potentially associated with prenatal stress in mothers, alters neuroanatomical development, contributing to behavioral problems in offspring.…”
Section: Neuroanatomicalsupporting
confidence: 56%
“…The fact that Davis et al [24, 25] reported harmful side effects after 1 course of ACS treatment as well as the subgroup analysis in our study that showed an effect on myelin, even in the STG, further reinforces the need to carefully balance the benefits and risks of ACS treatment.…”
Section: Discussionsupporting
confidence: 75%
“…Late preterm- or term-born infants after ACS exposure might therefore more specifically reveal effects from ACS as they are less likely to have deficits. Davis et al [24] reported that children who were full term at birth and had been exposed to 1 course of ACS had significant bilateral cortical thinning at 6–10 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported delayed overall brain growth, limbic systemspecific volumetric changes, and white matter abnormalities (Li et al, 2012;Lou et al, 1994;Qiu et al, 2013Qiu et al, , 2015Rifkin-Graboi et al, 2013). Such early observations appear to persist into childhood and adolescence, are correlated with affective problems, and may contribute to symptoms in patients with schizophrenia and autism (Buss et al, 2010(Buss et al, , 2012Davis et al, 2013;Du et al, 2013;Sarkar et al, 2014;Zikopoulos and Barbas, 2010).…”
Section: Reprogramming In the Prenatally Stressed Brainmentioning
confidence: 97%